Oxidative status of a yogurt-like fermented maize product containing phytosterols - Descalzo, Adriana Maria; Rizzo, Sergio Anibal; Servent, Adrien; Rossetti, Luciana; Lebrun, Marc; Perez, Carolina Daiana; Boulanger, Renaud; Mestres, Christian; Pallet, Dominique; Dhuique-Mayer, Claudie (2018)
This work describes the formulation of a functional yogurt-like product based on fermented maize with added phytosterols and its oxidative stability during cold storage. The technological challenge was to stabilize 3.5% esterified phytosterols (between 2 and 3 g of free sterols) in a low-fat emulsion and to preserve the obtained product throughout processing and storage. The natural bioactive compounds: lutein, zeaxanthin, β-cryptoxanthin, β-carotene and γ-tocopherol were detected in the yogurt, and remained stable during 12 days of refrigeration. Higher content of C18:1 n-9 and C18:3 n-3 (six and ninefold, respectively) were obtained in samples with phytosterols. This was desirable from a nutritional point of view, but at the same time it induced lipid oxidation that was 1.4-fold higher in the product with phytosterols than in the controls. The use of a multivariate approach served to find descriptors which were related to treatments, and to explain their behavior over time.